'Your country needs you': the ethics of allocating staff to high-risk clinical roles in the management of patients with COVID-19. Issue 7 (14th May 2020) - Dunn, Michael; Sheehan, Mark; Hordern, Joshua; Turnham, Helen Lynne; Wilkinson, Dominic
Abstract : As the COVID-19 pandemic impacts on health service delivery, health providers are modifying care pathways and staffing models in ways that require health professionals to be reallocated to work in critical care settings. Many of the roles that staff are being allocated to in the intensive care unit and emergency department pose additional risks to themselves, and new policies for staff reallocation are causing distress and uncertainty to the professionals concerned. In this paper, we analyse a range of ethical issues associated with changes to staff allocation processes in the face of COVID-19. In line with a dominant view in the medical ethics literature, we claim, first, that no individual health professional has a specific, positive obligation to treat a patient when doing so places that professional at risk of harm, and so there is a clear ethical tension in any reallocation process in this context. Next, we argue that the changing asymmetries of health needs in hospitals means that careful consideration needs to be given to a stepwise process for deallocating staff from their usual duties. We conclude by considering how a justifiable process of reallocating professionals to high-risk clinical roles should be configured once those who are 'fit for reallocation' have been identified. We claim that this process needs to attend to three questions that we consider in detail: (1) how the choice to make reallocation decisions is made, (2) what justifiable models for reallocation might look like and (3) what is owed to those who are reallocated.